2017
DOI: 10.1093/mnras/stx802
|View full text |Cite
|
Sign up to set email alerts
|

Far-ultraviolet observation of the globular cluster NGC 6397

Abstract: We present an observational far-UV (FUV) and near-UV (NUV) study of the core region of the globular cluster NGC 6397. The observations were obtained with the Space Telescope Imaging Spectrograph (STIS, FUV), and the Wide Field Camera 3 (WFC3, NUV) on board the Hubble Space Telescope. Here, we focus on the UV bright stellar populations such as blue stragglers (BSs), white dwarfs (WDs) and cataclysmic variables (CVs). We present the first FUV − NUV color-magnitude diagram (CMD) for this cluster. To support our c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Gap objects are the stars which are located between the MS and white dwarf (WD) sequence in the optical and UV CMDs. The CVs are expected to lie in this region as pointed out by Haurberg et al (2010), Dieball et al (2010) and Dieball et al (2017) in their study of M15, M80 and NGC 6397 respectively. We have found one bright gap object which is marked as orange star in Figures 2-6.…”
Section: Gap Objectsmentioning
confidence: 79%
See 1 more Smart Citation
“…Gap objects are the stars which are located between the MS and white dwarf (WD) sequence in the optical and UV CMDs. The CVs are expected to lie in this region as pointed out by Haurberg et al (2010), Dieball et al (2010) and Dieball et al (2017) in their study of M15, M80 and NGC 6397 respectively. We have found one bright gap object which is marked as orange star in Figures 2-6.…”
Section: Gap Objectsmentioning
confidence: 79%
“…Recent studies of GCs (Ferraro et al 2003;Haurberg et al 2010;Dieball et al 2010;Schiavon et al 2012;Piotto et al 2015;Parada et al 2016;Raso et al 2017;Dieball et al 2017) have shown that Ultra-Violet (UV) CMDs are important tools for identifying and studying the properties of UV bright stellar populations such as BSSs and HBs. Schiavon et al (2012) generated FUV−NUV vs FUV CMD of 44 GCs using GALEX data.…”
Section: Introductionmentioning
confidence: 99%
“…NGC 6397 is a nearby (D = 2.44 ± 0.04 kpc, Baumgardt et al 2019b) metal-poor, core-collapsed GC, whose close proximity has attracted significant study of its white dwarf and low-mass stellar populations (Paresce et al 1995;Cool et al 1996;Taylor et al 2001;Hansen et al 2007). In addition, NGC 6397 has 15 known CV candidates, a quiescent LMXB (qLMXB), and 1-2 MSPs (Cool et al 1995;Grindlay et al 2001;Cohn et al 2010;Dieball et al 2017). We locate 11 wellfitting snapshots from the model, N4-RV1-RG8-Z0.01.…”
Section: Ngc 6397mentioning
confidence: 99%
“…Signs of optical/UV variability can be helpful to further confirm the nature of the source, especially for CV identifications, since most CVs appear as blue variable stars (see e.g. Cool et al 1998;Edmonds et al 2003b;Dieball et al 2017;Rivera Sandoval et al 2018).…”
Section: Optical Variabilitymentioning
confidence: 99%